2005
DOI: 10.1111/j.1432-1033.1982.tb06922.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Action of Triphenyltin on Proton Conduction by the H+-ATPase of Mitochondria

Abstract: A study is presented of the action of triphenyltin on the kinetics of the anaerobic relaxation of the proton gradient set up by respiration in various type of 'inside-out' inner membrane vesicles obtained by exposure of beef-heart mitochondria to ultrasonic energy.Triphenyltin is shown to act as a powerful inhibitor of the proton conductivity of the H+-ATPase. The inhibition persists after removal of the ATPase protein inhibitor, F 1 and the oligomycin-sensitivity conferral protein (OSCP) from the particles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…1 A show the effect of 3 mM arsenitethis corresponds to the concentration of the reagent effective on thiol-depending dehydrogenases [18,19]-on the cycle of respiration-driven proton uptake and subsequent anaerobic proton releasc in ESMP. The arsenical, in contrast to oligomycin and triphenyltin (see Table 1 and [14]) which inhibited anaerobic proton release, caused a marked acceleration of the process. The extent of aerobic proton uptake did not decrease, evidently due to stimulatory effect of arsenite also on the rate of respiration-driven proton uptake (see also Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 A show the effect of 3 mM arsenitethis corresponds to the concentration of the reagent effective on thiol-depending dehydrogenases [18,19]-on the cycle of respiration-driven proton uptake and subsequent anaerobic proton releasc in ESMP. The arsenical, in contrast to oligomycin and triphenyltin (see Table 1 and [14]) which inhibited anaerobic proton release, caused a marked acceleration of the process. The extent of aerobic proton uptake did not decrease, evidently due to stimulatory effect of arsenite also on the rate of respiration-driven proton uptake (see also Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This substance causes an inhibition of proton conduction which does not change with time and does not perturb the kinetic pattern of the process (cf. [14]). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fungicide acts as a multi-site inhibitors, prevents spore germination and inhibits the metabolism of fungi, particularly respiration, inhibits oxidative phosphorylation in mitochondria and induces lipid peroxidation. Low concentrations of organostannic compounds inhibit the translocation of H + bound to the membrane, H +ATPase and ions such as Na + and K + (Papa et al, 1982;Powers & Beavis, 1991). Lawrence et al (2007a) while testing the fungicides Quadris ® and 2.08SC Topsin M ® to control bolls rot found that foliar spraying of fungicide 2-4 times during flowering increased the cotton yield.…”
Section: Chemical Control Of Cotton Bolls Rotmentioning
confidence: 99%